Kondisi Metereologi Saat Pengamatan Hilal 1 Syawal 1438H di Indonesia: Upaya Peningkatan Kemampuan Pengamatan dan Analisis Data Hilal - Fuad Thohari; Achmad Sasmito; Andy ES; Jaya Murjaya; Rony Kurniawan (AHKAM : Jurnal Ilmu Syariah, 2017)
Hilal observation done The Agency of Meteorology, Climatology,and Geophysics (BMKG) on June 24, 2017 at 17 Station Observations ofBMKG for the determination of 1 Shawwal 1438 H get the sighting the moon at Kupang Geophysical station. The result was still questioned by astronomers because in addition to their smaller size in terms of theory, it was also regarded as noise (disturbance). Re-observation at Kupang Geophysical Station withVixen ED81S telescope and Canon 500D detector obtained data that the newmoon position was in line with the calculation result (elongation 4˚ 49 '58 ")with smaller diameter than the theoretical value (67%). This article showed that the incident was suspected as a result of refraction so that the atmosphere seemed to function as a concave lens that resulted in the reduction of the object from its original size. DOI: 10.15408/ajis.v17i1.6224